Penguatan Identitas dan Aksesibilitas UMKM melalui Digitalisasi Lokasi Usaha di Google Maps sebagai Strategi Digital dalam Meningkatkan Jangkauan Konsumen - Rahmanida, Sabrina Eka; Rahmawati, Restiana Dwi; Nikmah, Richa Mulin; Naasyiroh, Rizqi Imroatun; Rahmawati, Riska (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Digitalization is an important strategy for MSMEs in increasing competitiveness and reaching a wider market. Cakeandme Cookies, an MSME located at Jl. Tosaren 2 RT 19 RW 07, Kediri, faces challenges in introducing its products to new customers due to limited access to information about business locations. This community service activity aims to help the MSME increase its business visibility by creating a business location on Google Maps. The method used is Participatory Action Research (PAR) with stages of socialization, mentoring, and direct implementation in creating and optimizing business profiles. The results of the activity show that after registering on Google Maps, there was an increase in the number of location searches and visits to the store. Digitalization of business locations has proven effective in increasing accessibility and customer trust in the brand. This implementation is expected to be a model for other MSMEs in adopting digital technology.